2013
DOI: 10.1021/ie303598e
|View full text |Cite
|
Sign up to set email alerts
|

Granular Flow in Silo Discharge: Discrete Element Method Simulations and Model Assessment

Abstract: Discharge dynamics of granular particles from a flat-bottomed silo is studied using both continuum modeling and three-dimensional (3D) discrete element method (DEM) simulations. Using DEM, the influence of microscopic parameters (interparticle friction coefficient, particle-wall friction coefficient and particle coefficient of restitution) and system parameters (orifice width) on the discharge rate is quantified. The spatial extent of different regimes (quasi-static, intermediate and inertial) of granular rheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…When different size particles are produced during the granulation process and the hopper is filled with such particles, in order to improve the discharge performance, an accurate prediction of the discharge flow pattern, rate and stability is highly important . Anand et al studied the effects of some single variables on the discharge rate and concluded that the effect of particle size on the discharge rate was minimal.…”
Section: Introductionmentioning
confidence: 99%
“…When different size particles are produced during the granulation process and the hopper is filled with such particles, in order to improve the discharge performance, an accurate prediction of the discharge flow pattern, rate and stability is highly important . Anand et al studied the effects of some single variables on the discharge rate and concluded that the effect of particle size on the discharge rate was minimal.…”
Section: Introductionmentioning
confidence: 99%
“…It has been validated as an efficient method in physical, geographic or engineering (Cheng et al, A c c e p t e d M a n u s c r i p t Implementing Discrete Element Method for Large-scale Simulation of Particles on Multiple GPUs 5 2003; Ferdowsi et al, 2014;Peters et al, 2005;Vidyapati & Subramaniam, 2013). In the most conventional formulation of DEM, the Voigt model is applied at each contact point in both the normal and tangential directions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2.1(b) shows that the discharge rate predicted from continuum simulations deviates considerably (more than 80%) from the Beverloo correlation (Beverloo et al, 1961) and DEM data. The discharge rate from a silo is controlled by the complex rheology of granular flow due to co-existence of different flow regimes (Vidyapati and Subramaniam, 2012b). This complex behavior makes it very difficult to formulate a comprehensive macroscale theory for granular stress tensor, which can describe all the flow regimes.…”
Section: Classification Of Granular Rheology In Different Regimesmentioning
confidence: 99%
“…This phenomenon of regime transition has been observed in many industrial and practical applications such as discharge of granular particles from silos or hoppers. It also affects the discharge rate from these devices (Vidyapati and Subramaniam, 2012b). However, the mechanisms of regime transition have not been fully understood in spite of many studies in both engineering and physics communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation